Diseño de planta para la producción de biodiesel a partir de aceite de fritura reciclado. - Terán Saldaña, Frank Arturo (2011)
Chapter I, the Biodiesel market study is done, in order to estimate the supply and demand for the product, as well as justify the possibility of installing a chemical plant for this purpose. This study was based on statistical data related to the consumption of Biodiesel, taking basically into account the Regulation of the Law for the Promotion of Biofuels Market, as being a relatively new product on the market has little data historical reference to consumption. Chapter II, the design selection process is discussed, and aims to choose a type of manufacturing process among existing, which is the most convenient and adaptable to our reality. For this purpose different processes are analyzed highlighting its main features for each of these. These processes will be subjected to an analysis of the technical and economic type to select the most appropriate Chapter III, aims to determine the choice of the most suitable place for installing the plant, for this use of the technique known as balancing factors, which consists of assigning numerical values to different factors both primary and secondary done. Chapter IV, includes the design of major equipment, such as tanks, pumps and reactors for use will be made of the spreadsheet in Excel. Chapter V, this chapter refers to the part of the instrumentation and automatic control, here it defined the type of control to use and illustrate both control loops used. Chapter VI, This chapter deals with processing aids such as water, steam, fuel and electricity; also it includes storage facilities, security, and laboratory buildings. Chapter VII, based on the distribution of plant and basically defines the spatial arrangement of all operating units, for which the unit and master plan were developed. Chapter VIII, this chapter an economic study is carried out to determine the profitability of the project. Chapter IX, In this chapter the conclusions of the study are presented. Chapter X, shows the bibliographical references. Chapter XI, in the appendix, where they develop in detail Chapters 2 and 4 is presented.